The BIOPROSPECTING OF PONTIANAK’S ALOE VERA AS AN INDONESIAN PLANT FOR COSMECEUTICAL : A REVIEW - Farisa Qisthi Shafara; Budi Irawan; Ernah Ernah (Universitas Tadulako, 2023)
Pontianak Aloe Vera (PAV) is one of the plants in Indonesia that is used as an icon of the city of Pontianak. This plant is widely planted in Kalimantan and is known for its medicinal and cosmetic benefits. The method used is reference search through Google Scholar, Research Gate and other electronic media and then analyzed by descriptive method. The articles reviewed in Indonesian or English language, which published between 2010 to 2022, relevantly. Based on the research results, this plant contains various chemical compounds, such as aloemoedin, aloebarbadiod, vitamin C, collagen, polysaccharides, enzymes, and minerals that have the potential as cosmeceuticals. The products made from Aloe vera produced by the researchers are in the form of external use products in the form of gels, creams, lotions, liquid soaps, and so on for skin and hair care and the use of products orally in the form of powders. These treatment products are reported to have benefits as an anti-dandruff and hair growth stimulate. In addition, other benefits on the skin are maintaining moisture and hydration of the skin, as a sunscreen, stimulating the growth of fibroblasts to treat wounds after surgery, brightening the skin, fading wounds and acne scars, reducing the severity of acne and maintaining skin elasticity.